2011
DOI: 10.1200/jco.2011.36.8902
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcome of Male Breast Cancer: An International Population-Based Study

Abstract: A B S T R A C T PurposeMale breast cancer is a rare disease with an incidence rate less than 1% of that of female breast cancer. Given its low incidence, few studies have assessed risk and prognosis. MethodsThis population-based study, including 459,846 women and 2,665 men diagnosed with breast cancer in Denmark, Finland, Geneva, Norway, Singapore, and Sweden over the last 40 years, compares trends in incidence, relative survival, and relative excess mortality between the sexes. ResultsWorld standardized incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
153
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(202 citation statements)
references
References 26 publications
23
153
4
11
Order By: Relevance
“…(Kaushik et al, 2014) Most Western studies have reported a 5 year OS of greater than 60% whereas results of Asian and African countries have shown a 5 year OS ranging from 40-60%. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Sedighi et al, 2013) Our 5 year OS was 61.1% which was consistent with most of the South Asian studies as well as Western studies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…(Kaushik et al, 2014) Most Western studies have reported a 5 year OS of greater than 60% whereas results of Asian and African countries have shown a 5 year OS ranging from 40-60%. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Sedighi et al, 2013) Our 5 year OS was 61.1% which was consistent with most of the South Asian studies as well as Western studies.…”
Section: Discussionsupporting
confidence: 85%
“…This can be attributed to factors such as lack of screening mammography and public awareness. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Kaushik et al, 2014) The average age at diagnosis in our population was 52 years with 7 of our patients falling in the age group 50 to 55. This was 5 years younger than the age of diagnosis of women with FBC in Pakistan.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Breast cancer mortality among women has declined during the last decades because of improvements in diagnostic procedures and treatment, but the corresponding observation has not been made in male breast cancer. 1 Recent studies have indicated that males have a poorer survival than females, despite having received adjuvant treatment to the same extent. 2,3 In addition, studies on transcriptional and genomic levels have revealed important molecular differences between male and female breast cancer.…”
mentioning
confidence: 99%
“…Other studies reported that when matched by stage and age, men with breast cancer appeared to have a comparable or better prognosis than women (48). However, perhaps due to poor awareness of the disease and diagnostic delays, several studies argued that MBC with higher stage tumors and had a poorer overall prognosis (49).…”
Section: Discussionmentioning
confidence: 99%